A Qualitative Exploration of Coordinators' and Carers' Perceptions of the Healthy Eating, Active Living (HEAL) Programme in Residential Care. (23rd February 2017) - Cox, Rachael; Skouteris, Helen; Fuller‐Tyszkiewicz, Matthew; McCabe, Marita; Watson, Brittany; Fredrickson, Julia; Jones, Amanda D.; Omerogullari, Stella; Stanton, Kelly; Bromfield, Leah; Hardy, Louise L.
Abstract : Internationally, there are few studies that have trialled structured intervention programmes designed to prevent excessive weight gain or combat existing overweight/obesity for young people living in out‐of‐home care. The Healthy Eating, Active Living (HEAL) programme was designed to address this limitation and is, to our knowledge, the first programme that simultaneously encourages young people and their carers to engage in a healthy lifestyle. This is the second of two papers presenting the HEAL evaluation. The aim of this study was twofold: first, to explore the experiences and opinions of key stakeholders regarding the intervention programme; and second, to understand the key enablers and barriers to successful implementation of the HEAL programme in residential care. Seventeen carers and ten programme coordinators participated in semi‐structured interviews. Findings demonstrated that HEAL was considered a valuable adjunct to the residential care programme, and was successful in raising awareness about the importance of leading a healthy lifestyle. Positive behaviour change among the young people and carers' dietary, physical activity and sleeping habits, and the development of independent living skills were described. Barriers to implementation included leadership support and professional development of carers. Recommendations are made to improve implementation, particularly around the importance of increasing stakeholder 'buy‐in'. Copyright © 2017 John Wiley & Sons, Ltd. Key Practitioner Messages: There is a need to address the lifestyle habits of young people in residential care. Raising awareness is an important first step, but must be supplemented with supportive environmental change to enable lasting, healthy outcomes. Carer capabilities need to be strengthened so that they can effectively manage challenging behaviours, yet still address the lifestyle habits of young people in care. Stakeholder 'buy‐in' and a programme champion are critical to implementation of healthy lifestyle programmes in residential care. 'The first programme that simultaneously encourages young people and their carers to engage in a healthy lifestyle'